The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 38 nurses is usually the lower of the two. As in the case of health visitors, there appears to be no guiding principle in determining salaries, and even in London, there is no Whitley Council scale for school nurses. In London, the whole of the school medical work is carried out by the London County Council, and the scale adopted for their school nurses is £100, rising by £10 per annum to £120 with the addition of bonus on the Civil Service scale. This is at present equal to £171 10s. to £198 8s. The maximum salary is thus lower than the minimum salary paid to a health visitor in London. We have no complete information as to the conditions of service of school nurses throughout the country, such as we have in the case of health visitors, but as far as our information goes, minimum salaries outside London range from £140 to £190 per annum, with possibly a few exceptional cases at an oven lower salary. Maximum salaries are rarely over £200 per annum. Holidays are usually longer in the case of school nurses than for health visitors, in some cases covering the whole of the elementary school holidays. Payment during absence on sick leave, superannuation, etc., is substantially the same as for health visitors. TUBERCULOSIS VISITORS. QUALIFICATIONS. The qualifications demanded from tuberculosis visitors vary according to the work which they are called upon to perform, and to the preferences of individual local authorities. In some cases, general nursing training only is required, while in others considerable importance is attached to training and/or experience in public health and social work, with or without nursing training. Nursing experience in a sanatorium is considered an extra qualification by some local authorities — others require the full qualifications of a health visitor. The certificate of the Sanitary Inspectors' Examination Board is frequently held by tuberculosis visitors, and some sanitary inspectors act as tuberculosis visitors. DUTIES. The duties of a tuberculosis visitor include some or all of the following :— 1. Attendance at tuberculosis dispensaries to assist the tuberculosis officer. 2. Accompanying the tuberculosis officer on his visits to patients in their own homes. 3. Home visiting of patients on receipt by the medical officer of health of the first notification of tuberculosis from the medical practitioner attending the case. 4. Periodical re-visits. 5. Reporting infringements of the Public Health Act (e.g., sanitary defects of premises, and overcrowding to the medical officer of health. 6. Arranging for the periodical examination of other members of the patient's family by the tuberculosis officer. 7. Reporting to the tuberculosis officer cases in which extra milk, eggs, and butter, and/or additional beds, bedding or shelters are required. 8. Reporting on the general home conditions of patients admitted to or discharged from hospital or sanatorium ; arranging for the disinfection of premises, bedding, etc. 9. Help and advice in connection with re-housing. The personal influence and advice of the tuberculosis visitor who is in personal contact 126/TG/RES/X/1036A/14